The Influence of Progressive Muscle Relaxation (PMR) on the Improvement of Body Composition, Depression Status and Quality of Life of Breast Cancer Patients During Chemotherapy in Dr. Mohammad Hoesin General Hospital Palembang - Ronaldoe B; Mulawan Umar; Irfannuddin (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Background: The breast cancer progression and chemotherapy side effects not only cause problems in mental status, but also the patient's physical status. This is related to a deteriorating quality of life and a worse prognosis. Physical exercise can improve physical status, mental status, and quality of life. Methods: Experimental pre- and post intervention research with a control group was conducted on breast cancer patients to determine the effect of progressive muscle relaxation on the improvement of body composition, depression status, and quality of life for breast cancer patients during chemotherapy at RSMH on February 2019 - February 2020. Results: Progressive muscle relaxation (PMR) can improve body composition (p = 0.000), reduce the degree of depression (p = 0.000), improve global health status (p = 0.013), physical functioning (p = 0.002), emotional functioning (p = 0.009), social functioning (p = 0015), body image (0.000), sexual function (p = 0.05), future perspective (p = 0.006), and decreased fatigue (p = 0.00), nausea and vomiting (p = 0.002 ), pain (0.000), insomnia (0.002), appetite loss (p = 0.000), breast symptoms (p = 0.000), arm symptoms (p = 0.000), hair loss (p = 0.000), and therapy side effects (p = 0.000). Conclusion: Progressive muscle relaxation has a significant effect on improving body composition, depression status, and quality of life for breast cancer patients during chemotherapy.